Artificial Intelligence and Educational Psychology in Love-Based Arabic Language Learning: A Literature Review - Mohamad Aris Murtadho; Ahmad Fikri Amrullah (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Learning Arabic as a Foreign Language (AFL) involves linguistic, pedagogical, and affective challenges, particularly foreign language anxiety. Artificial Intelligence (AI) can support personalization and immediate feedback, yet overly technology-centered instruction may weaken human interaction. This study aims to formulate a conceptual model integrating AI, educational psychology, and a love-based curriculum for holistic, learner-centered AFL learning. A qualitative-descriptive systematic literature review examined 26 scholarly sources, comprising recent peer-reviewed studies and foundational works, retrieved from Scopus, Web of Science, ERIC, Google Scholar, Garuda, and SINTA. The sources were synthesized through Braun and Clarke's six-stage thematic analysis. The findings indicate that AI supports diagnosis, personalization, adaptive practice, and feedback; educational psychology guides motivation, emotional regulation, autonomy, competence, relatedness, and cognitive-load management; and the love-based curriculum provides an ethical foundation for empathy, psychological safety, and meaningful teacher-student relationships. The study proposes an AI-Psychology-Love Synergy Model comprising diagnosis-personalization, interactive implementation, and feedback-adaptation. The model positions AI as an assistant that strengthens, rather than replaces, the teacher's human role.